A review of Sarcocystis spp. shed by opossums (Didelphis spp.) in Brazil - Valadas, Samantha Yuri Oshiro Branco; Soares, Rodrigo Martins; Lindsay, David Scott (Brazilian Journal of Veterinary Research and Animal Science, 2016)
South American opossums are the definitive hosts of Sarcocystis neurona, Sarcocystis falcatula, Sarcocystis speeri and Sarcocystis lindsayi. The sporocysts of these species of Sarcocystis are morphologically similar and methods like infectivity and pathogenicity for intermediate hosts (immunodeficient mice and psittacine birds) and molecular tools are used for identification. Opossums are synanthropic wild animals, and widely distributed in Brazilian territory. Previous studies have shown high environmental contamination with S. neurona sporocysts in several Brazilian regions. This paper reviews information on Sarcocystis spp. shed by various opossum species and its occurrence in Brazil.